Iranian Nurses' Experiences of Workplace Violence in Prehospital Emergency Care: A Qualitative Study. (April 2020) - Rahmani, Azad; Dadashzadeh, Abbas; Hassankhani, Hadi; Boyle, Malcolm; Mohammadi, Eesa; Campbell, Suzanne
Abstract : Prehospital emergency care nurses experience severe workplace violence. However, despite the widespread violence they experience, this phenomenon has not been well studied among these nurses. Therefore, the purpose of this study was to explore the experiences of Iranian nurses working in prehospital setting regarding workplace violence with a focus on the factors leading to such violence. In this qualitative descriptive study, 23 prehospital nurses participated purposefully. The data were collected by individual face-to-face semistructured interviews and analyzed using content analysis methodology. Data analysis led to the identification of 4 main themes, including job competency mismatch, inadequate resources, criticality of the situation and circumstances, and inadequate awareness and misplaced expectations of society. These nurses have not completed specialized training courses, work in a system that is in a critical situation, and face many barriers and deficiencies in terms of intra- and interorganizational coordination. On the other hand, people in the community do not have sufficient awareness about the duties and services provided by prehospital nurses and thus have unrealistic expectations to receive services. The results showed that there was a deep gap between the prehospital emergency realities and public expectations, leading to workplace violence. Therefore, efforts to improve the working conditions of nurses with an emphasis on teaching specialized prehospital emergency courses, especially violence control courses, promoting intra- and interorganizational coordination, and increasing the equipment and personnel of ambulances for special missions, as well as raising the public awareness and outlining more realistic expectations, may reduce the prevalence of violence against prehospital nurses.